Efeitos dos alimentos funcionais no tecido muscular esquelético de ratos expostos cronicamente a fumaça de cigarro - CAETANO, Heliard Rodrigues dos Santos (2017)
Male Wistar rats were randomly divided into eight groups (n = 8). The animals were fed standard diet, or supplemented with probiotic, prebiotic and symbiotic and exposed or not to passive smoking. After 180 days of exposure to cigarette smoke, samples from the soleus muscle were collected for histological analysis and after staining with Hematoxylin Eosin, the captured images were submitted to fractal dimension analysis. For normality of the data by the Shapiro Wilk test, and analysis of variance (ANOVA), post test of Tukey (p <0.05). The results revealed a significant increase in the fractal dimension of the HE stained section of the soleus muscle of rats poisoned by chronic exposure to cigarette smoke. The groups supplemented with functional, probiotic, prebiotic and symbiotic foods and smokers presented a significant decrease in the fractal dimension when compared to the smoking control group and did not differ from the non - smoking experimental groups (p> 0.05). The results obtained provide convincing evidence that chronic exposure to passive smoking in rats, as an experimental model in vivo, induces inflammatory changes. Functional foods, probiotic, prebiotic and symbiotic, and supplemented in the diet, bioremediation the inflammation, due to chronic passive exposure to smoking. The fractal dimension revealed to be a tool capable of quantifying inflammatory alterations in the soleus skeletal muscle.